TADIC INTERNACIONALIZACIÓN DE CONFLICTOS INTERNOS Y RESPONSABILIDAD INDIVIDUAL RAFAEL A. PRIETO SANJUÁN Pontificia Universidad Javeriana; Biblioteca JurídicaDiké, 2005, Bogotá Colombia Colección Grandes Fallos de la Justicia Penal Internacional N°1 - González Jácome, Jorge; Pontificia Universidad Javeriana (2005)
null